Between research and memory: Leggenda by Alessandro Solbiati (Itinera, 2022)
The article examines Alessandro Solbiati’s second theatrical work, Leggenda, which takes inspiration from the tale “The Grand Inquisitor” included in Dostoevsky’s novel The Karamazov Brothers. After presenting the meaning of this tale in the novel of the Russian writer, it reconstructs the genesis of the opera and the structure of the libretto. Then it analyses the musical forms, the vocal language and the composer’s ‘pensée sonorielle’ and considers them in the light of his musical dramaturgy. Finally, it outlines Solbiati’s aesthetical conception, his relationship with the musical tradition and his personal stance on postmodernism and postwebernian avant-garde.